1999
DOI: 10.1093/emboj/18.5.1270
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Raf/MAP kinase cascade by the Ras-related protein TC21 is required for the TC21-mediated transformation of NIH 3T3 cells

Abstract: TC21 is a member of the Ras superfamily of small GTP-binding proteins and, like Ras, has been implicated in the regulation of growth-stimulating pathways. Point mutations introduced into TC21 based on equivalent H-Ras oncogenic mutations are transforming in cultured cells, and oncogenic mutations in TC21 have been isolated from several human tumours. The mechanism of TC21 signalling in transformation is poorly understood. While activation of the serine/threonine kinases Raf-1 and B-Raf has been implicated in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 37 publications
(81 reference statements)
5
62
1
Order By: Relevance
“…This experiment was performed three times and similar results were observed Even though all three Raf genes can be activated by oncogenic Ras and target the same downstream molecules to pass on their signals, they have di erent biological and biochemical properties and their functions are noncompensatable (Muszynski et al, 1995;Pritchard et al, 1995;Marias et al, 1997). A-Raf and Raf-1 behave in a more similar fashion than B-Raf (Fabian et al, 1993;Marias et al, 1995Marias et al, , 1997Pritchard and McMahon, 1997;Vossler et al, 1997;Hagemann and Rapp, 1999;Rosario et al, 1999). In our studies, we observed that after 24-h of b-estradiol deprivation, ectopic activation of either Raf-1 or A-Raf were able to induce cell proliferation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This experiment was performed three times and similar results were observed Even though all three Raf genes can be activated by oncogenic Ras and target the same downstream molecules to pass on their signals, they have di erent biological and biochemical properties and their functions are noncompensatable (Muszynski et al, 1995;Pritchard et al, 1995;Marias et al, 1997). A-Raf and Raf-1 behave in a more similar fashion than B-Raf (Fabian et al, 1993;Marias et al, 1995Marias et al, , 1997Pritchard and McMahon, 1997;Vossler et al, 1997;Hagemann and Rapp, 1999;Rosario et al, 1999). In our studies, we observed that after 24-h of b-estradiol deprivation, ectopic activation of either Raf-1 or A-Raf were able to induce cell proliferation.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, in murine cells the kinase activities of both Raf-1 and A-Raf were stimulated by Ras and Src. However, B-Raf kinase activity was controlled by Ras and other members of the small G protein family such as Rap1 in PC12 cells (Vossler et al, 1997) or TC21 in NIH3T3 cells (Marias et al, 1997;Rosario et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The Ras to Raf to MEK to MAPK pathway has been thought to be a simple linear pathway. Recently, COT1 has been shown to activate MEK (Hagemann et al, 1999), TC21 has been shown to activate Raf (Rosario et al, 1999), MKP-1 regulates c-Raf and MAPK (Shapiro and Ahn, 1998). Clearly there are`branches' in the pathway and it may be that other molecules may also participate in the MAPK cascade in ways that have not been observed to date.…”
Section: Discussionmentioning
confidence: 99%
“…Both phosphorylated and unphosphorylated ERK1 and ERK2 proteins were detected by immunoblotting with ERK1 antibody (Santa Cruz Biotechnology, Inc., Santa Cruz, CA). The blot membranes were then stripped as described (48) and were reprobed using a monoclonal antibody specific for the phosphorylated forms of ERK1 and ERK2 (New England Biolabs, catalog no. 9106S) followed by development with ECL (Pierce) using the manufacturer's protocol.…”
Section: Cellmentioning
confidence: 99%